Physicochemical atributes and quality of the Melipona scutellaris honey: comparison with Brazilian regulatory standards - Medeiros, Aldo Cunha; Medeiros, Vanessa Fátima Lima Paiva; Rego, Amália Cínthia Meneses; Araújo-Filho, Irami; Medeiros, Vitor Brasil (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2016)
Objective: The aim this study was to compare the physicochemical characteristics of the honey of wild Melipona scutellaris with the standards determined by the technical regulations and honey quality of Ministry of Agriculture, Brazil. Methods: Honey of Melipona scutellaris was acquired from certified institution in Natal, RN, Brazil. The physicochemical analysis of honey was carried out so that all parameters were derived from the average of three replications. Moisture of the samples was determined by refractometer. The Hydroxymethylfurfural proof was determinined by the absorbance using a digital spectrometer, with a range of 200-1000 nm and band crossing 5 nm. The ash content of the samples was determined in a muffle furnace. Digital pHmeter was used for measurement of pH and total acidity by the method of simple titration. Insoluble solids in water were determined by stove use. All these parameters were compared with those established by Technical Regulation of Ministry of Agriculture, Brazil, 2000, for honey identity and quality. Honey microbiological analysis was done using the blood agar and agar McConkey selective media. Results: The physicochemical analysis of the Melipona scutellaris honey demonstrated that all parameters were in accordance with the standards established by the Ministry of Agriculture, Brazil regulations, and could be considered of good quality for research and human consumption. The microbiological examination revealed that the honey had no bacterial contamination. Conclusion: Our findings suggest that the physicochemical composition of M. scutellaris honey is compatible with the Brazilian guidelines for the composition and quality of honey.